An object–pressure–endurance–resilience system for assessing the vulnerability of coastal zone ecosystems. (August 2022) - Liu, Bo; Han, Rong; Tang, Liang; Cheng, Xi
Highlights: Constructed an O-P-E-R index system ("object–pressure–endurance–resilience"). Proposed a combined subjective and objective weight determination method by combining GAHP and the entropy weight method. Improved the traditional matter-element evaluation model and proposed a coastal zone ecosystem vulnerability assessment model. A viable basis for the development of coastal zone ecological management policies. Completed a vulnerability assessment of coastal zone ecosystems in the Bohai Sea region. Abstract: As a zone of interaction between land and sea, coastal zones are important carriers of the marine economy, and they are the focal point for strategies related to strengthening a country by means of the sea. As the coastal zones are where land and sea are most closely linked, they become a strategic area for achieving sustainable expansion of the blue economic space. Coastal zones have some capacity to cope with and recover from the adverse effects of ecological pressure, which is the coastal zone ecosystem vulnerability. However, given the vulnerability of coastal zone ecosystems and the existence of considerable ecological pressure, it is necessary to systematically assess coastal zones' vulnerability and propose targeted countermeasures. First of all, this paper uses normative research methods and the methods that combine quantitative research with qualitative research to investigate the assessment of coastal zone ecosystem vulnerability and propose solutions for related governance. Second, based on an analysis of the shortcomings of existing methods, this study constructed an index system based on "object–pressure–endurance–resilience" (O-P-E-R) to assess coastal zone ecosystem vulnerability. O-P-E-R takes into account the triad of nature–society–culture and systematically defines ecosystem vulnerability. In the meantime, a combined weight calculation method that considers subjective and objective weights was proposed based on an improved group analytic hierarchy process (GAHP) method and the entropy weight method. Further, based on the standardization and normalization of indicator values, a method and scale for assessing coastal zone ecosystem vulnerability were proposed based on an improved matter-element model. In conclusion, the research has established a coastal zone ecosystem vulnerability assessment system that not only expand the safety management of coastal zone ecosystems but also provide a theoretical basis for governments to formulate related policies.